Global Search to Understand the Impact of the scenario of the Keyword - Dr. D Bujji Babu, K. Jayakrishna, Mr.Sk.Anjaneyulu Babu, Dr. R. Saran Kumar, Alhaf Malik. K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to globalization, the world became a global village, the computer-based search playing a vital role in understanding the scenarios around the globe. Only one solution to explore search engine data is Google Trends, which is at free of cost, and potential to predict the official data immediately. In this paper, we experimented with a keyword-based search to understand various scenarios in different countries. We, analyzed the Google Trends using various techniques like long short-term memory in feed forward networks in Deep Learning, Multi linear regression and Elastic net, SVR and Time Series algorithms for analysis